Evaluation the Relationship between Oral Contraceptives Containing Drospirenone with Dyslipidemia and Risk of Cardiovascular Diseases among Women in Al-kut City - Haider Hafudh Humaish1 , Amer Alasadi2 ,Intithar Aldafae3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Chronic and prolong use of oral contraceptives (OCs) may lead to appearance of undesirable effects inwomen who used these drugs. There are many types of contraceptives, some contain estrogen and the othercontain progesterone, or combination of them in the same drug. This work was performed in a population ofadult females to study the relationship between the chronic use of OCs with dyslipidemia and the threat ofcardiac diseases. A total 163 volunteers were participated in this study, and, their aged between 21-42 yearsold. In addition, all women were free of heart disease, dyslipidemia and any hormonal disturbance accordingto their health records. They were categorized into three differnt groups, the control group included 52unmarried women and does not use any OCs, group A: included 57 women took OCs (combination pillestrogen and progestin) for less than 6 months, and group B contained 54 women used OCs for more than oneyear. We meassued lipid profile, and blood indices of cardiovascular disease, like Creatine Kinase-MB (CKMB), insulin, Lactate Dehydrogenase (LDH) albumin, leptin and HbA1c test. In addition, we determined thecoronary risk index, atherogenic Coefficient, and an atherogenic index . Our results recorded a significantincrease in total cholesterol, LDL, coronary risk index (TC/HDL), LDH and HbA1c in group2 comparedto compared to control group. Furthermore, our data demonstrated no clear differences in Triglyceride,leptin hormone, TG, HDL, insulin, albumin and CK-MB in group2 compared to control. Moreover, thedata indicated a significant elevation in the concentration of leptin hormone, LDH, HbA1c, TC, TG, LDL,coronary risk index , atherogenic Coefficient and Atherogenic index, and significant decline in HDL andalbumin in group B compared with control group. Therefore, we concluded that oral contraceptive coulddeter the lipid profile status and some enzyme related to the cardiovascular system. These alterations conveya possible risk for the development of cardiac diseases. Routine screeing of lipid tests would be measured inwomen used OCs for long periods to avoid any potential risk of cardiac diseases.